South Asian Qur'an Commentaries and Translations: A Preliminary Intellectual History. (1st April 2020) - Tareen, SherAli
Abstract : This essay presents a broad overview of certain key works and intellectual trends that mark traditional scholarship on the Qur'an in South Asia, from the late medieval to the modern periods, roughly the fourteenth to the mid-twentieth centuries. Far from an exhaustive survey of any sort, what I have attempted instead is a preliminary and necessarily partial outline of the intellectual trajectory of Qur'an commentaries and translations in the South Asian context—in Arabic, Persian, and Urdu—with a view to exploring how shifting historical and political conditions informed new ways of engaging the Qur'an. My central argument is this: in South Asia, the early modern and modern periods saw an important shift from largely elite scholarship on the Qur'an, invariably conducted by scholars intimately bound to the imperial order of their time, to more selfconsciously popular works of translation and exegesis designed to access and attract a wider non-elite public. In this shift, I argue, translation itself emerged as an important and powerful medium of hermeneutical populism pregnant with the promise of broadening the boundaries of the Qur'an's readership and understanding. In other words, as the pendulum of political sovereignty gradually shifted from pre-colonial Islamicate imperial orders to British colonialism, new ways of imagining the role, function, and accessibility of the Qur'an also came into central view. A major emphasis of this essay is on the thought and contributions of the hugely influential eighteenth-century scholar Shah Wali Ullah (d. 1762) and his family on the intellectual topography of South Asian Qur'an commentaries and translations.